STUDY OF THE EFFICIENCY OF DIFFERENT PLANT RAW MATERIAL ENSILAGING WITH APPLICATION OF LACTOBACILLUS AS PRESERVING AGENT - Ibraimova, Zh. K.; Rustenov, A.R; Eleugaliyeva, N.Zh.; Oleksievich, E.A. (Eurasian Journal of Applied Biotechnology, 2013)
The value of silos in feeding farm animals is still high and now it is almost impossible to compose high-producing cows rations without the combined silage. Despite the considerable range of plant raw material for silage, not so many cultures possess practical significance. Most regions of the country, particularly the Southern regions, use corn as the main crop for sialge, and in recent years for this purpose there has been used Sudan grass as well - one of the most common and promising forage crops in the southern latitudes. It differs with its drought resistance , relatively high and stable yield of green mass , the ability to grow quickly after cutting and abilityto give its viable seeds in favorable years. Up to date, there have not been highlighted issues on impact of the use of silage from Sudan grass and Sudan grass in a mixture of annual and perennial crops in rations of highly-producing cows on metabolism, digestion,milk production indicators , the quality of milk and dairy products. Therefore, biotechnological and physiological and biochemical aspects of conservation and utilization of the combined silage in the ration of high-producing cows is an actual problem. Feeding is a crucial factor that affects the productivity of dairy cows. The maximum detection of the genetic potential of animal productivity can be achieved through balanced rational feeding, which depends on proper science-based organization of fodder base for animal livestock. Unfortunately, in Kazakhstan, the interest to strengthening of fodder base for animal livestock has significantly weakened.Reduction of the area under fodder crops has led to a significant shortage of feed and, consequently, to a decrease in the number of animals and their poor productivity. Recovering of the lost ground in the animal livestock industry is impossible without strengthening the fodder base of any farm regardless of the form of management. From this point of view, ensialging is a economically effective. There have been conducted researches on the effectiveness of ensilaging of different plant raw materials using lactic acid bacteria as a preservative (Lactobacillus acidophilus, L. sasei, L. Plantarum 52). It is found that L. Plantarum 52 bacterium, one of the studied bacteria for legumes ensilaging, is mostly suitable. And the gap in the flowering between the silage made of new-mown raw material and original silage mass comprises, %: alfalfa - 2.53-3.25, ekspartseta - at 1,51-2,05, yellow sweet clover at 1,87-2,41 corn and 1.61 - 3.16%.